A sodium ion battery
By matching the crystallinity of the carbon material of the negative electrode material and the solvent content in the electrolyte in the sodium ion battery, the problem of insufficient fast charging performance and low-temperature performance of the sodium ion battery is solved, and the performance improvement and application promotion of the battery is achieved.
Patent Information
- Application Number
- CN202211511423.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-29
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2042-11-29
AI Technical Summary
Sodium ion batteries have shortcomings in fast charging performance and low-temperature performance, especially the fast charging performance does not have advantages, which affects the application promotion of batteries.
By matching and limiting the crystallinity of the carbon material of the negative electrode material and the solvent content in the electrolyte, the ratio of the crystallinity of the carbon material to the solvent content is within the range of 0.010≤X/Y≤0.170, so as to improve the rate performance of the sodium ion battery and low temperature performance.
It effectively improves the fast charging and low-temperature performance of sodium ion batteries, reduces the impedance of the battery, improves the overall performance of the battery, and promotes the promotion of its applications.
Smart Images

Figure BDA0003971000740000111
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of batteries, and in particular relates to a sodium ion battery. Background Art
[0002] Renewable energy such as solar energy and wind energy are greatly affected by the geographical environment, and are intermittent and unevenly distributed in time and space, and need to be converted through energy storage technology. Sodium-ion batteries have resource and cost advantages and have development potential in the field of electrochemical energy storage. On the power supply side of the power system, electrochemical energy storage technology needs to adjust the output of power plants according to power demand. Under conditions of sufficient energy, the battery is charged at a faster rate to reduce the phenomenon of "abandoning wind and light", adjust the fluctuations of renewable energy generation, and improve the quality of electricity.
[0003] In the field of electrochemical energy storage, lithium-ion batteries are the most widely used, which have high energy density but insufficient safety performance. With the development of new energy vehicles, more and more attention is paid to the safety of batteries. Sodium-ion batteries have been paid attention to by battery manufacturers in recent years due to their higher safety. However, sodium-ion batteries currently do not have an advantage in fast charging performance. Therefore, sodium-ion batteries need to be improved to improve their rate charging performance. Summary of the invention
[0004] The present invention is based on the inventors' discovery and understanding of the following facts and problems: the transmission speed of sodium ions in the negative electrode and the film formation at the negative electrode interface affect the fast charging performance and low-temperature performance of sodium ion batteries. Therefore, in-depth research is needed to enable sodium ion batteries to obtain excellent fast charging performance while improving low-temperature performance.
[0005] The present invention aims to solve one of the technical problems in the related art to at least a certain extent. To this end, an embodiment of the present invention provides a sodium ion battery, which effectively improves the rate performance of the sodium ion battery by matching the negative electrode material and the solvent in the electrolyte, and improves the low temperature performance of the sodium ion battery, which is conducive to the promotion and application of the sodium ion battery.
[0006] A sodium ion battery according to an embodiment of the present invention comprises: a positive electrode, a negative electrode and an electrolyte, wherein the negative electrode comprises a negative electrode active material comprising a carbon material, the crystallinity of the carbon material is X%, the electrolyte comprises a solvent, and the mass percentage of the solvent in the electrolyte is Y%, wherein X and Y satisfy the relationship 0.010≤X / Y≤0.170.
[0007] Advantages and technical effects of the sodium ion battery of the embodiment of the present invention:
[0008] In the embodiment of the present invention, the carbon material in the negative electrode of the sodium ion battery and the solvent content in the electrolyte are matched and limited. This is because, for the carbon material negative electrode of the sodium ion battery, during the charge and discharge process, capacity storage is achieved by filling, adsorbing and embedding sodium ions in the negative electrode. The inventors found that the crystallinity of the negative electrode material affects the transmission rate of sodium ions in the negative electrode. Low crystallinity is conducive to the filling and adsorption of sodium ions, which can achieve rapid transmission of sodium ions and improve the fast charging performance of the battery; high crystallinity carbon materials are conducive to the embedding of sodium ions, resulting in slower sodium ion transmission at the negative electrode, which is not conducive to the fast charging performance of the battery; and for the electrolyte in the battery, the inventors further found that if the solvent content in the electrolyte is too high, it will cause the interface film to thicken. If a low crystallinity carbon material is matched at the same time, the solvent decomposition will be aggravated, further leading to an increase in the thickness of the interface film, thereby reducing the ion transmission rate at the interface, thereby reducing the fast charging performance of the battery; but if the solvent content in the electrolyte is too low, the viscosity of the electrolyte will increase, which will be unfavorable for the low temperature performance of the battery, resulting in a decrease in the low temperature performance of the battery. Therefore, the inventors discovered through research that controlling the crystallinity of the carbon material in the negative electrode and the content of the solvent in the electrolyte at 0.010≤X / Y≤0.170 can effectively improve the transmission of sodium ions inside the negative electrode and the interface transmission, reduce the impedance of the battery, and improve the low-temperature performance of the battery while improving the fast charging performance of the battery.
[0009] In some embodiments, X and Y satisfy the relationship 0.020≤X / Y≤0.120.
[0010] In some embodiments, the crystallinity X% of the carbon material is 1%≤X%≤15%, preferably 2%≤X%≤14%; and / or the mass percentage Y% of the solvent in the electrolyte is 70%≤Y%≤90%, preferably 75%≤Y%≤85%.
[0011] In some embodiments, the crystallinity X% of the carbon material is 2%≤X%≤8%, the mass percentage content Y% of the solvent in the electrolyte is 80%≤Y%≤85%, and X and Y satisfy the relationship 0.020≤X / Y≤0.100.
[0012] In some embodiments, the carbon material includes at least one of hard carbon or soft carbon.
[0013] In some embodiments, the solvent includes at least one of carbonates, carboxylates, and ethers.
[0014] In some embodiments, the carbonates include cyclic carbonates or chain carbonates having 3 to 5 carbon atoms; preferably, the cyclic carbonates include at least one of ethylene carbonate, vinylene carbonate, vinylethylene carbonate, propylene carbonate, γ-butyrolactone, and butylene carbonate; the chain carbonates include at least one of dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, and dipropyl carbonate;
[0015] The carboxylic acid esters include carboxylic acid esters with carbon atoms of 2 to 6, preferably, the carboxylic acid esters include at least one of methyl acetate, ethyl acetate, propyl acetate, butyl acetate, propyl propionate, and ethyl propionate;
[0016] The ethers include cyclic ethers or chain ethers having 4 to 10 carbon atoms; preferably, the cyclic ether includes at least one of 1,3-dioxolane, 1,4-dioxolane, tetrahydrofuran, 2-methyltetrahydrofuran, and 2-trifluoromethyltetrahydrofuran; the chain ether includes at least one of dimethoxymethane, 1,2-dimethoxyethane (DME), diethylene glycol dimethyl ether, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, and tetraethylene glycol dimethyl ether.
[0017] In some embodiments, the solvent includes at least one of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, ethyl propionate, propyl propionate, γ-butyrolactone, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, and tetraethylene glycol dimethyl ether.
[0018] In some embodiments, the electrolyte further includes electrolyte salt and additives, wherein:
[0019] The electrolyte salt includes at least one of sodium hexafluorophosphate, sodium bis(trifluoromethane)sulfonyl imide, sodium trifluoromethanesulfonate, sodium tetrafluoroborate, and sodium perchlorate;
[0020] The additive includes at least one of fluorinated carbonates, cyclic carbonates, cyclic sulfonates, cyclic sulfates, phosphates, borates or nitrile compounds; preferably, the fluorinated carbonate includes at least one of fluoroethylene carbonate or difluoroethylene carbonate; preferably, the cyclic carbonate includes at least one of vinylene carbonate, ethylene vinylene carbonate, methylene vinylene carbonate; the cyclic sulfonate includes at least one of 1,3-propane sultone, 1,4-butane sultone, allyl-1,3-sultone; the cyclic sulfate includes at least one of ethylene sulfate, 4-methyl ethylene sulfate, propylene sulfate; the phosphate includes at least one of triallyl phosphate, trimethyl phosphate, triethyl phosphate, tris(trimethylsilyl) phosphate; the borate includes at least one of tris(trimethylsilyl) borate or tris(triethylsilyl) borate; the nitrile compound includes at least one of succinonitrile, glutarodinitrile, ethylene glycol bis(propionitrile) ether, hexane trinitrile, adiponitrile, pimelonitrile, suberonitrile, azelaonitrile or sebaconitrile.
[0021] In some embodiments, the positive electrode includes a positive electrode active material, and the positive electrode active material includes at least one of layered transition metal oxides, Prussian compounds, phosphate compounds, sulfate compounds, wherein,
[0022] The chemical formula of the layered transition metal oxide is Na x M y O z , 0 < x ≤ 1, 0 < y ≤ 1, 1 < z ≤ 2, M is selected from at least one of Cr, Fe, Co, Ni, Cu, Mn, Sn, Mo, Sb, V; preferably, the transition metal oxide is selected from at least one of NaNi m Fe n Mn p O2 (m + n + p = 1, 0 ≤ m ≤ 1, 0 ≤ n ≤ 1, 0 ≤ p ≤ 1) or NaNimConMnpO2 (m + n + p = 1, 0 ≤ m ≤ 1, 0 ≤ n ≤ 1, 0 ≤ p ≤ 1);
[0023] The molecular formula of the Prussian material is Na x M[M′(CN)6] y ·zH2O, M and M′ are transition metals, 0 < x ≤ 2, 0 < y ≤ 1, 0 < z ≤ 20; preferably, the Prussian material is selected from at least one of NaxMn[Fe(CN)6] y ·zH2O or Na x Fe[Fe(CN)6] y ·zH2O;
[0024] The chemical formula of the phosphate is Na3(MO 1-xPO4)2F 1+2x , 0≤x≤1, M is selected from at least one of Al, V, Ge, Fe, and Ga, preferably, the phosphate is selected from at least one of Na3(VPO4)2F3 or Na3(VOPO4)2F; or, the chemical formula of the phosphate is Na2MPO4F, M is selected from at least one of Fe and Mn, preferably, the phosphate is selected from at least one of Na2FePO4F or Na2MnPO4F;
[0025] The chemical formula of the sulfate is Na2M(SO4)2·2H2O, where M is selected from at least one of Cr, Fe, Co, Ni, Cu, Mn, Sn, Mo, Sb, and V. DETAILED DESCRIPTION
[0026] Embodiments of the present invention are described in detail below. The embodiments are exemplary and intended to be used to explain the present invention, but should not be construed as limiting the present invention.
[0027] A sodium ion battery according to an embodiment of the present invention comprises: a positive electrode, a negative electrode and an electrolyte, wherein the negative electrode comprises a negative electrode active material comprising a carbon material, the crystallinity of the carbon material is X%, the electrolyte comprises a solvent, and the mass percentage of the solvent in the electrolyte is Y%, wherein X and Y satisfy the relationship 0.010≤X / Y≤0.170.
[0028] Specifically, the crystallinity of the carbon material is defined as the ratio of the C(002) crystal plane diffraction peak area of the material in XRD to the sum of the areas of the amorphous peak and the C(002) crystal plane diffraction peak; the diffraction peak intensity ratio is tested by the XRD method.
[0029] The sodium ion battery of the embodiment of the present invention matches and limits the carbon material in the negative electrode of the sodium ion battery and the solvent content in the electrolyte. This is because, for the carbon material negative electrode of the sodium ion battery, during the process of charging and discharging, the capacity storage is achieved by the filling, adsorption and embedding of sodium ions in the negative electrode. The inventor found that the crystallinity of the negative electrode material affects the transmission rate of sodium ions in the negative electrode. Low crystallinity is conducive to the filling and adsorption of sodium ions, which can achieve rapid transmission of sodium ions and improve the fast charging performance of the battery; high crystallinity carbon materials are conducive to the embedding of sodium ions, resulting in slower sodium ion transmission at the negative electrode, which is not conducive to the fast charging performance of the battery. As for the electrolyte in the battery, the inventor further found that if the solvent content in the electrolyte is too high, it will cause the interface film to thicken. If the carbon material with low crystallinity is matched at the same time, the solvent decomposition will be aggravated, resulting in an increase in the thickness of the interface film, thereby reducing the ion transmission rate of the interface, thereby reducing the fast charging performance of the battery; but if the solvent content in the electrolyte is too low, the viscosity of the electrolyte will increase, which will be unfavorable to the low temperature performance of the battery, resulting in a decrease in the low temperature performance of the battery. Therefore, the inventors discovered through research that controlling the crystallinity of the carbon material in the negative electrode and the content of the solvent in the electrolyte at 0.010≤X / Y≤0.170 can effectively improve the transmission of sodium ions inside the negative electrode and the interface transmission, reduce the impedance of the battery, and improve the low-temperature performance of the battery while improving the fast charging performance of the battery.
[0030] In some embodiments, preferably, X and Y satisfy the relationship 0.020≤X / Y≤0.120. In the embodiment of the present invention, the relationship between X and Y is optimized, which is conducive to further improving the rate performance and low temperature performance of the sodium ion battery. If the value of X / Y is too low, it means that a relatively low crystallinity carbon material is used in the battery to match a high concentration of solvent. Although the low crystallinity carbon material can improve the transmission kinetics of sodium ions inside the negative electrode and improve the fast charging performance of the battery, the solvent content in the electrolyte is too high, causing the interface film to thicken, and the low crystallinity carbon material used will aggravate the solvent decomposition, further increase the thickness of the interface film, reduce the ion transmission rate of the interface, and cause the fast charging performance of the battery to decrease. If the value of X / Y is too high, it means that a relatively high crystallinity carbon material is used in the battery to match a relatively low concentration of solvent. The use of high crystallinity carbon materials will cause the ion transmission inside the negative electrode to lag and deteriorate the fast charging performance of the battery. At the same time, the solvent content used in the electrolyte is too low, which will cause the viscosity of the electrolyte to increase, thereby causing the low temperature performance of the battery to decrease.
[0031] In some embodiments, the crystallinity X% of the carbon material is 1%≤X%≤15%, preferably 2%≤X%≤14%. In the embodiments of the present invention, the crystallinity of the carbon material is further preferred. If the crystallinity of the carbon material in the negative electrode is too low, although the ion transmission rate in the negative electrode can be improved, the decomposition of the solvent will be aggravated, resulting in an increase in the thickness of the interface film, which is not conducive to improving the fast charging performance of the battery; if the crystallinity of the carbon material is too high, the sodium ions will be transmitted slowly in the negative electrode, reducing the fast charging performance of the battery.
[0032] In some embodiments, the mass percentage Y% of the solvent in the electrolyte is 70%≤Y%≤90%, preferably 75%≤Y%≤85%. In the embodiments of the present invention, the content of the solvent in the electrolyte is further optimized. If the solvent content is too high, the solvent consumption at the interface increases, causing the interface film to thicken, which is not conducive to the transmission of sodium ions and leads to a decrease in the fast charging performance of the battery; if the solvent content is too low, the viscosity of the electrolyte increases, thereby reducing the low temperature performance of the battery.
[0033] In some embodiments, the crystallinity X% of the carbon material is 2%≤X%≤8%, the mass percentage of the solvent in the electrolyte Y% is 80%≤Y%≤85%, and X and Y satisfy the relationship 0.020≤X / Y≤0.100. In the embodiment of the present invention, the crystallinity and solvent content of the carbon material and the relationship X / Y between the two are further optimized, which is conducive to further improving the fast charging performance and rate performance of the sodium ion battery. The 3C charging capacity can reach 83%, and the low-temperature discharge capacity retention rate at -20°C can reach 76%, with excellent performance.
[0034] In some embodiments, the carbon material includes at least one of hard carbon or soft carbon. In the embodiments of the present invention, there is no particular limitation on the carbon material, and the hard carbon or soft carbon used in the sodium ion battery can be applied to the battery in the embodiments of the present invention.
[0035] In some embodiments, the solvent includes at least one of carbonates, carboxylates, and ethers.
[0036] In some embodiments, the carbonates include cyclic carbonates or chain carbonates having 3 to 5 carbon atoms; preferably, the cyclic carbonates include at least one of ethylene carbonate, vinylene carbonate, vinylethylene carbonate, propylene carbonate, γ-butyrolactone, and butylene carbonate; the chain carbonates include at least one of dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, and dipropyl carbonate;
[0037] The carboxylic acid esters include carboxylic acid esters with carbon atoms of 2 to 6, preferably, the carboxylic acid esters include at least one of methyl acetate, ethyl acetate, propyl acetate, butyl acetate, propyl propionate, and ethyl propionate;
[0038] The ethers include cyclic ethers or chain ethers having 4 to 10 carbon atoms; preferably, the cyclic ether includes at least one of 1,3-dioxolane, 1,4-dioxolane, tetrahydrofuran, 2-methyltetrahydrofuran, and 2-trifluoromethyltetrahydrofuran; the chain ether includes at least one of dimethoxymethane, 1,2-dimethoxyethane (DME), diethylene glycol dimethyl ether, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, and tetraethylene glycol dimethyl ether.
[0039] In the embodiment of the present invention, there is no particular restriction on the solvent in the electrolyte, and any solvent applicable to the sodium ion electrolyte can be used in the present invention. Preferably, the solvent includes at least one of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, ethyl propionate, propyl propionate, γ-butyrolactone, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, and tetraethylene glycol dimethyl ether.
[0040] In some embodiments, the electrolyte further includes electrolyte salts and additives. The embodiments of the present invention have no particular restrictions on the electrolyte salts and additives. All electrolyte salts and additives applicable to sodium ion electrolytes can be applicable to the present invention.
[0041] Preferably, the electrolyte salt includes at least one of sodium hexafluorophosphate, sodium bis(trifluoromethane)sulfonyl imide, sodium trifluoromethanesulfonate, sodium tetrafluoroborate, and sodium perchlorate.
[0042] Preferably, the additive includes at least one of fluorocarbonate, cyclic carbonate, cyclic sulfonate, cyclic sulfate, phosphate, borate or nitrile compounds; further preferably, the fluorocarbonate includes at least one of fluoroethylene carbonate or difluoroethylene carbonate; the cyclic carbonate includes at least one of vinylene carbonate, vinyl ethylene carbonate and methylene carbonate; the cyclic sulfonate includes at least one of 1,3-propane sultone, 1,4-butane sultone and propenyl-1,3-sultone. The cyclic sulfate comprises at least one of vinyl sulfate, 4-methyl vinyl sulfate and propylene sulfate; the phosphate comprises at least one of tripropargyl phosphate, trimethyl phosphate, triethyl phosphate and tris(trimethylsilane) phosphate; the borate comprises at least one of tris(trimethylsilane) borate and tris(triethylsilane) borate; the nitrile compound comprises at least one of succinonitrile, glutaronitrile, ethylene glycol bis(propionitrile) ether, hexanetrinitrile, adiponitrile, pimelonitrile, suberonitrile, azelaic acid dinitrile and sebaconitrile.
[0043] In some embodiments, the positive electrode includes a positive electrode active material. In the embodiments of the present invention, there is no particular limitation on the positive electrode active material, and any positive electrode active material applicable to sodium-ion batteries can be used in the batteries of the embodiments of the present invention.
[0044] Preferably, the positive electrode active material includes at least one of layered transition metal oxides, Prussian compounds, phosphate compounds, and sulfate compounds.
[0045] More preferably, the chemical formula of the layered transition metal oxide is Na x M y O z , where 0 < x ≤ 1, 0 < y ≤ 1, 1 < z ≤ 2, and M is selected from at least one of Cr, Fe, Co, Ni, Cu, Mn, Sn, Mo, Sb, and V. More preferably, the transition metal oxide is selected from at least one of NaNi m Fe n Mn p O2 (m + n + p = 1, 0 ≤ m ≤ 1, 0 ≤ n ≤ 1, 0 ≤ p ≤ 1) or NaNimConMnpO2 (m + n + p = 1, 0 ≤ m ≤ 1, 0 ≤ n ≤ 1, 0 ≤ p ≤ 1);
[0046] More preferably, the chemical formula of the Prussian material is Na x M[M′(CN)6] y ·zH2O, where M and M′ are transition metals, 0 < x ≤ 2, 0 < y ≤ 1, 0 < z ≤ 20; more preferably, the Prussian material is selected from at least one of NaxMn[Fe(CN)6] y ·zH2O or Na x Fe[Fe(CN)6] y ·zH2O;
[0047] More preferably, the chemical formula of the phosphate is Na3(MO 1-x PO4)2F 1+2x , where 0 ≤ x ≤ 1, and M is selected from at least one of Al, V, Ge, Fe, and Ga. More preferably, the phosphate is selected from at least one of Na3(VPO4)2F3 or Na3(VOPO4)2F; or the chemical formula of the phosphate is Na2MPO4F, where M is selected from at least one of Fe and Mn. More preferably, the phosphate is selected from at least one of Na2FePO4F or Na2MnPO4F;
[0048] The chemical formula of the sulfate is Na2M(SO4)2·2H2O, where M is selected from at least one of Cr, Fe, Co, Ni, Cu, Mn, Sn, Mo, Sb, and V.
[0049] In the embodiment of the present invention, the preparation of the positive electrode or negative electrode of the sodium ion battery can be carried out according to the method commonly used in the art for preparing the positive electrode or negative electrode of the sodium ion battery, without any particular limitation. For example, the active materials of the positive and negative electrodes can be mixed with the conductive agent and the adhesive, and the mixture can be dispersed in an organic solvent to prepare a slurry, and then the slurry can be coated on the current collector and dried and rolled. Among them, the conductive agent, adhesive, organic solvent and current collector used can all be materials and substances commonly used in the art, which will not be repeated here.
[0050] The present invention is described in detail below with reference to embodiments.
[0051] Example 1
[0052] Preparation of electrolyte: Ethylene carbonate (solvent), ethyl methyl carbonate (solvent), NaPF6 (electrolyte salt), and FEC (additive fluoroethylene carbonate) are prepared into a non-aqueous electrolyte in a mass ratio of 25:60:13:2, wherein the mass percentage of the solvents ethylene carbonate and ethyl methyl carbonate in the electrolyte is 85%.
[0053] Preparation of negative electrode: The negative electrode active material hard carbon, the conductive agent carbon black, the solvent water, and the binder sodium carboxymethyl cellulose are mixed evenly to obtain a negative electrode slurry, and the negative electrode slurry is coated on the current collector. After coating, drying, and rolling processes, a negative electrode sheet is prepared, wherein the hard carbon has a crystallinity of 5%.
[0054] Preparation of positive electrode: binder polyvinylidene fluoride, solvent N-methylpyrrolidone, conductive agent acetylene black, positive electrode active material NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2 is mixed evenly to obtain a positive electrode slurry, the positive electrode slurry is coated on a current collector, and a positive electrode sheet is prepared through coating, drying, and rolling processes.
[0055] Assembling sodium-ion batteries: The prepared positive electrode sheet, negative electrode sheet and PP separator are prepared into battery cells, which are then baked, injected with electrolyte, and packaged to obtain sodium-ion batteries.
[0056] Example 2
[0057] The method is the same as that of Example 1, except that the solvent content of the electrolyte and the crystallinity of the carbon material in the negative electrode are different. The details are as follows:
[0058] Preparation of electrolyte: Ethylene carbonate, ethyl methyl carbonate, NaPF6 and FEC are prepared into a non-aqueous electrolyte in a mass ratio of 20:50:28:2, wherein the solvent content in the electrolyte is 70%.
[0059] The active material of the negative electrode is hard carbon, and the crystallinity of the hard carbon is 1%.
[0060] Example 3
[0061] The method is the same as that of Example 1, except that the crystallinity of the carbon material in the negative electrode is different. Specifically, the active material of the negative electrode is hard carbon, and the crystallinity of the hard carbon is 2%.
[0062] Example 4
[0063] The method is the same as that of Example 1, except that the solvent content of the electrolyte and the crystallinity of the carbon material in the negative electrode are different. The details are as follows:
[0064] Preparation of electrolyte: Ethylene carbonate, ethyl methyl carbonate, NaPF6 and FEC are prepared into a non-aqueous electrolyte in a mass ratio of 30:60:8:2, wherein the solvent content in the electrolyte is 90%.
[0065] The active material of the negative electrode is hard carbon, and the crystallinity of the hard carbon is 3%.
[0066] Example 5
[0067] The method is the same as that of Example 1, except that the solvent content of the electrolyte and the crystallinity of the carbon material in the negative electrode are different. The details are as follows:
[0068] Preparation of electrolyte: Ethylene carbonate, ethyl methyl carbonate, NaPF6 and FEC are prepared into a non-aqueous electrolyte in a mass ratio of 20:60:18:2, wherein the solvent content in the electrolyte is 80%.
[0069] The active material of the negative electrode is hard carbon, and the crystallinity of the hard carbon is 4%.
[0070] Example 6
[0071] The method is the same as that of Example 1, except that the solvent content of the electrolyte and the crystallinity of the carbon material in the negative electrode are different. The details are as follows:
[0072] Preparation of electrolyte: Ethylene carbonate, ethyl methyl carbonate, NaPF6 and FEC are prepared into a non-aqueous electrolyte in a mass ratio of 20:55:23:2, wherein the solvent content in the electrolyte is 75%.
[0073] The active material of the negative electrode is hard carbon, and the crystallinity of the hard carbon is 6%.
[0074] Example 7
[0075] The method is the same as that of Example 1, except that the crystallinity of the carbon material in the negative electrode is different. Specifically, the active material of the negative electrode is hard carbon, and the crystallinity of the hard carbon is 8%.
[0076] Example 8
[0077] The method is the same as that of Example 1, except that the crystallinity of the carbon material in the negative electrode is different. Specifically, the active material of the negative electrode is hard carbon, and the crystallinity of the hard carbon is 10%.
[0078] Example 9
[0079] The method is the same as that of Example 1, except that the crystallinity of the carbon material in the negative electrode is different. Specifically, the active material of the negative electrode is hard carbon, and the crystallinity of the hard carbon is 14%.
[0080] Example 10
[0081] The method is the same as that of Example 1, except that the solvent content of the electrolyte and the crystallinity of the carbon material in the negative electrode are different. The details are as follows:
[0082] Preparation of electrolyte: Ethylene carbonate, ethyl methyl carbonate, NaPF6 and FEC are prepared into a non-aqueous electrolyte in a mass ratio of 30:60:8:2, wherein the solvent content in the electrolyte is 90%.
[0083] The active material of the negative electrode is hard carbon, and the crystallinity of the hard carbon is 15%.
[0084] Embodiment 11
[0085] The method is the same as that of Example 1, except that the carbon material in the negative electrode is soft carbon, and the crystallinity of the soft carbon is 5%.
[0086] Example 12
[0087] The method is the same as that of Example 1, except that the solvent content of the electrolyte and the carbon material in the negative electrode are different. The details are as follows:
[0088] Preparation of electrolyte: Ethylene carbonate, ethyl methyl carbonate, NaPF6 and FEC are prepared into a non-aqueous electrolyte in a mass ratio of 20:55:18:2, wherein the solvent content in the electrolyte is 75%.
[0089] The active material of the negative electrode is soft carbon, and the crystallinity of the soft carbon is 6%.
[0090] Example 13
[0091] The method is the same as that of Example 1, except that the solvent in the electrolyte is only ethylene carbonate, with a mass content of 85%.
[0092] Embodiment 14
[0093] The method is the same as that in Example 1, except that the solvent in the electrolyte is only ethyl methyl carbonate, and the mass content of ethyl methyl carbonate in the electrolyte is 85%.
[0094] Embodiment 15
[0095] The method is the same as that in Example 1, except that the solvents in the electrolyte are propyl propionate and ethylene glycol dimethyl ether, the mass content of propyl propionate in the electrolyte is 25%, and the mass content of ethylene glycol dimethyl ether is 60%.
[0096] Example 16
[0097] The method is the same as that in Example 1, except that the solvents in the electrolyte are propyl propionate and ethylene glycol diethyl ether, the mass content of propyl propionate in the electrolyte is 25%, and the mass content of ethylene glycol diethyl ether is 60%.
[0098] Embodiment 17
[0099] The method is the same as that in Example 1, except that the solvents in the electrolyte are propyl propionate, ethylene glycol dimethyl ether and ethylene glycol diethyl ether, the mass content of propyl propionate in the electrolyte is 25%, the mass content of ethylene glycol dimethyl ether is 30%, and the mass content of ethylene glycol diethyl ether is 30%.
[0100] Embodiment 18
[0101] The method is the same as that of Example 17, except that the solvent in the electrolyte is only propyl propionate, and the mass content of propyl propionate in the electrolyte is 85%.
[0102] Embodiment 19
[0103] The method is the same as that of Example 17, except that the solvent in the electrolyte is only ethylene glycol dimethyl ether, and the mass content of ethylene glycol dimethyl ether in the electrolyte is 85%.
[0104] Embodiment 20
[0105] The method is the same as that of Example 17, except that the solvent in the electrolyte is only ethylene glycol diethyl ether, and the mass content of ethylene glycol diethyl ether in the electrolyte is 85%.
[0106] Embodiment 21
[0107] The method is the same as that of Example 1, except that the solvent content of the electrolyte and the crystallinity of the carbon material in the negative electrode are different. The details are as follows:
[0108] Preparation of electrolyte: Ethylene carbonate, ethyl methyl carbonate, NaPF6 and FEC are prepared into a non-aqueous electrolyte in a mass ratio of 25:40:33:2, wherein the solvent content in the electrolyte is 65%.
[0109] The active material of the negative electrode is hard carbon, and the crystallinity of the hard carbon is 0.8%.
[0110] Embodiment 22
[0111] The method is the same as that of Example 1, except that the solvent content of the electrolyte and the crystallinity of the carbon material in the negative electrode are different. The details are as follows:
[0112] Preparation of electrolyte: Ethylene carbonate, ethyl methyl carbonate, NaPF6 and FEC are prepared into a non-aqueous electrolyte in a mass ratio of 32:60:6:2, wherein the solvent content in the electrolyte is 92%.
[0113] The active material of the negative electrode is hard carbon, and the crystallinity of the hard carbon is 15.5%.
[0114] Comparative Example 1
[0115] The method is the same as that of Example 1, except that the solvent content of the electrolyte and the crystallinity of the carbon material in the negative electrode are different. The details are as follows:
[0116] Preparation of electrolyte: Ethylene carbonate, ethyl methyl carbonate, NaPF6 and FEC are prepared into a non-aqueous electrolyte in a mass ratio of 30:60:8:2, wherein the solvent content in the electrolyte is 90%.
[0117] The active material of the negative electrode is hard carbon, and the crystallinity of the hard carbon is 0.5%.
[0118] Comparative Example 2
[0119] The method is the same as that of Example 1, except that the solvent content of the electrolyte and the crystallinity of the carbon material in the negative electrode are different. The details are as follows:
[0120] Preparation of electrolyte: Ethylene carbonate (EC), ethyl methyl carbonate (EMC), NaPF6 and FEC are prepared into a non-aqueous electrolyte in a mass ratio of 15:50:33:2, wherein the solvent content in the electrolyte is 65%.
[0121] The active material of the negative electrode is hard carbon, and the crystallinity of the hard carbon is 15%.
[0122] Comparative Example 3
[0123] The method is the same as that of Example 1, except that the solvent content of the electrolyte and the crystallinity of the carbon material in the negative electrode are different. The details are as follows:
[0124] Preparation of electrolyte: Ethylene carbonate, ethyl methyl carbonate, NaPF6 and FEC are prepared into a non-aqueous electrolyte in a mass ratio of 25:50:23:2, wherein the solvent content in the electrolyte is 75%.
[0125] The active material of the negative electrode is hard carbon, and the crystallinity of the hard carbon is 14%.
[0126] How to control carbon crystallinity:
[0127] Carbon materials with a crystallinity of 1% ≤ X% ≤ 15% need to be obtained by high-temperature carbonization. The carbon materials are prepared by high-temperature carbonization of the precursor. This method is a general method for preparing carbon materials. Specifically, the precursor is placed at a high temperature and the temperature is gradually increased to the carbonization temperature. The carbonization temperature range required for preparing carbon materials with a crystallinity of 1% ≤ X% ≤ 15% is in the range of 600°C to 2000°C. The temperature is kept for a certain period of time (0.5 to 24 hours) and the carbon materials are obtained after crushing. The crystallinity of the carbon material is related to the temperature control of the carbonization process. As the carbonization temperature increases, the crystallinity of the prepared carbon material increases; as the heating rate decreases, the crystallinity of the carbon material increases. The crystallinity of the carbon material can be adjusted by regulating the heating rate and the carbonization temperature. Among them, the carbonization temperature and the insulation time can be known in combination with the common knowledge in the field.
[0128] Taking Example 1 as an example, to prepare a carbon material with a carbon crystallinity of 5%, a carbonization temperature of 800° C., a heating rate of 15° C. / min, and a heat preservation time of 0.5 h are required, and the carbon material is obtained after crushing.
[0129] The fast charging performance and low temperature performance tests were performed on the lithium ion batteries prepared in Examples 1-22 and Comparative Examples 1-3. The test results are shown in Table 1.
[0130] (I) Fast charging performance test: Charge the formed sodium ion battery to 3.9V at 0.5C constant current at room temperature, then charge at constant voltage until the current drops to 0.03C, then discharge at 0.5C constant current to 1.5V, and record the charge capacity D1. Charge the battery to 3.9V at 3C constant current at room temperature, then charge at constant voltage until the current drops to 0.03C, then discharge at 0.5C constant current to 1.5V, and record the charge capacity D2. Battery 3C charge capacity percentage (%) = 3C charge capacity D2 / 0.5C charge capacity D1×100%.
[0131] (II) Low temperature discharge performance test: The formed sodium ion battery is charged to 3.9V at room temperature with a current constant current of 0.5C, then charged at a constant voltage until the current drops to 0.03C, and then discharged to 1.5V at a current constant current of 0.5C, and the room temperature discharge capacity D3 of the battery is recorded. Then the battery is charged to 3.9V at room temperature with a current constant current of 0.5C, then charged at a constant voltage until the current drops to 0.03C, then placed at -20℃ for 7h, and discharged to 1.5V at a current constant current of 0.5C, and the low temperature discharge capacity D4 and median voltage of the battery are recorded. The calculation formula is as follows: Battery low temperature discharge rate (%) = low temperature discharge capacity D4 / normal temperature discharge capacity D3 × 100%.
[0132] Table 1
[0133]
[0134] In Examples 1-22 of the present invention, the values of X and Y satisfy the relationship 0.010≤X / Y≤0.170, and the prepared sodium ion battery has good fast charging performance and low temperature performance. In particular, the sodium ion battery prepared in Example 1 has a rate charging capacity percentage of 85%, a low temperature discharge capacity retention rate of 78% and a low temperature discharge median voltage of 2.47V, and has excellent performance.
[0135] In Comparative Example 1, due to the low crystallinity of the hard carbon used and the high solvent content used in the electrolyte, the X / Y value is lower than 0.010, and the 3C charging capacity retention rate of the prepared lithium-ion battery is only 71%, and the rate charging performance is significantly lower than that of the embodiments of the present invention. This may be due to the excessively high solvent content in the electrolyte, which causes the thickening of the interface film, and the low crystallinity carbon material aggravates the decomposition of the solvent, further leading to an increase in the thickness of the interface film, reducing the ion transfer rate at the interface, which is not conducive to improving the fast charging performance of the battery.
[0136] In Comparative Example 2, the solvent content in the electrolyte is relatively low, and the carbon material used has a high degree of crystallinity, so that the X / Y value is higher than 0.170. The prepared sodium ion battery not only has a lower low-temperature discharge capacity retention rate and a lower median voltage than the embodiments of the present invention, but also has a lower 3C charging capacity than the embodiments of the present application. This may be because the high crystallinity of the carbon material causes the internal ion transport of the negative electrode to lag, thereby deteriorating the fast charging performance of the battery, and the solvent content in the electrolyte is too low, resulting in an increase in the viscosity of the electrolyte, thereby reducing the low temperature performance of the battery.
[0137] In Comparative Example 3, the crystallinity of the hard carbon used is 14%, and the content of the solvent in the electrolyte is 75%, both of which are within the preferred range of the crystallinity of the carbon material and the content of the electrolyte solvent in the embodiment of the present invention. However, since the ratio of the crystallinity of the carbon material to the content of the solvent in the electrolyte exceeds 0.170, a good match between the negative electrode material and the solvent cannot be achieved, resulting in a decrease in the fast charging performance and low temperature performance of the battery. This may be because the sodium ion battery using a carbon material with a higher crystallinity as the negative electrode has a slower embedding process in the crystallization zone than filling / adsorption, and the ion transport inside the negative electrode lags, resulting in a deterioration in the fast charging performance of the sodium battery; at the same time, the electrolyte solvent content is low, and the electrolyte viscosity increases, which further reduces ion diffusion and reduces the battery's rate performance and low temperature performance.
[0138] The inventors have found through extensive research that the fast charging performance of the battery is closely related to the content of the solvent in the electrolyte and the crystallinity of the negative electrode carbon material. In the embodiment of the present invention, the content of the solvent in the electrolyte and the crystallinity of the negative electrode carbon material are controlled to satisfy the relationship 0.010≤X / Y≤0.170, thereby effectively improving the fast charging performance of the battery and improving the low temperature performance.
[0139] In the present invention, the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" etc. mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the described specific features, structures, materials or characteristics may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0140] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A sodium ion battery, characterized in that: include: A positive electrode, a negative electrode and an electrolyte, wherein the negative electrode comprises a negative electrode active material comprising a carbon material, wherein the crystallinity of the carbon material is X%, 1%≤X%≤15%, and the electrolyte comprises a solvent, wherein the solvent comprises at least one of carbonates, carboxylates and ethers, and the mass percentage of the solvent in the electrolyte is Y%, 70%≤Y%≤90%, wherein X and Y satisfy the relationship 0.010≤X / Y≤0.
170.
2. The sodium ion battery according to claim 1, characterized in that X and Y satisfy the relationship 0.020≤X / Y≤0.
120.
3. The sodium ion battery according to claim 1 or 2, characterized in that: The crystallinity X% of the carbon material is 2%≤X%≤14%; and / or the mass percentage Y% of the solvent in the electrolyte is 75%≤Y%≤85%.
4. The sodium ion battery according to claim 3, characterized in that: The crystallinity X% of the carbon material is 2%≤X%≤10%, the mass percentage content Y% of the solvent in the electrolyte is 80%≤Y%≤85%, and X and Y satisfy the relationship 0.020≤X / Y≤0.
115.
5. The sodium ion battery according to claim 1, characterized in that: The carbon material includes at least one of hard carbon or soft carbon.
6. The sodium ion battery according to claim 1, characterized in that: The carbonates include cyclic carbonates or chain carbonates having 3 to 5 carbon atoms; The carboxylic acid esters include carboxylic acid esters having 2 to 6 carbon atoms; The ethers include cyclic ethers or chain ethers having 4 to 10 carbon atoms.
7. The sodium ion battery according to claim 6, characterized in that: The cyclic carbonate includes at least one of ethylene carbonate, vinylene carbonate, vinyl ethylene carbonate, propylene carbonate, γ-butyrolactone, and butylene carbonate; the chain carbonate includes at least one of dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, and dipropyl carbonate.
8. The sodium ion battery according to claim 6, characterized in that: The carboxylic acid ester includes at least one of methyl acetate, ethyl acetate, propyl acetate, butyl acetate, propyl propionate, and ethyl propionate.
9. The sodium ion battery according to claim 6, characterized in that: The cyclic ether includes at least one of 1,3-dioxolane, 1,4-dioxolane, tetrahydrofuran, 2-methyltetrahydrofuran, and 2-trifluoromethyltetrahydrofuran; the chain ether includes at least one of dimethoxymethane, 1,2-dimethoxyethane, diethylene glycol dimethyl ether, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, and tetraethylene glycol dimethyl ether.
10. The sodium ion battery according to claim 1 or 6, characterized in that: The solvent includes at least one of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, ethyl propionate, propyl propionate, γ-butyrolactone, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, and tetraethylene glycol dimethyl ether.
11. The sodium ion battery according to claim 1, characterized in that: The electrolyte also includes electrolyte salt and additives, wherein: The electrolyte salt includes at least one of sodium hexafluorophosphate, sodium bis(trifluoromethane)sulfonyl imide, sodium trifluoromethanesulfonate, sodium tetrafluoroborate, and sodium perchlorate; The additive includes at least one of fluorocarbonate, cyclic carbonate, cyclic sulfonate, cyclic sulfate, phosphate, borate or nitrile compounds.
12. The sodium ion battery according to claim 11, characterized in that: The fluorocarbonate includes at least one of fluoroethylene carbonate or difluoroethylene carbonate; the cyclic carbonate includes at least one of vinylene carbonate, ethylene carbonate, and methylene carbonate; the cyclic sulfonate includes at least one of 1,3-propane sultone, 1,4-butane sultone, and propenyl-1,3-sultone; the cyclic sulfate includes at least one of vinyl sulfate, 4-methyl vinyl sulfate, and propenyl sulfate; the phosphate includes at least one of tripropargyl phosphate, trimethyl phosphate, triethyl phosphate, and tris(trimethylsilane)phosphate; the borate includes at least one of tris(trimethylsilane)borate or tris(triethylsilane)borate; the nitrile compound includes at least one of succinonitrile, glutaronitrile, ethylene glycol bis(propionitrile) ether, hexanetrinitrile, adiponitrile, pimelonitrile, suberonitrile, azelaic acid nitrile, or sebaconitrile.
13. The sodium ion battery according to claim 1, characterized in that: The positive electrode includes a positive electrode active material, and the positive electrode active material includes at least one of a layered transition metal oxide, a Prussian compound, a phosphate compound, and a sulfate compound, wherein: The chemical formula of the layered transition metal oxide is Na x M y O z , 0<x≤1, 0<y≤1, 1<z≤2, M is selected from at least one of Cr, Fe, Co, Ni, Cu, Mn, Sn, Mo, Sb, and V; The molecular formula of the Prussian material is Na x M[M′(CN)6] y ·zH2O, M and M' are transition metals, 0 <x≤2,0<y≤1,0<z≤20; The chemical formula of the phosphate is Na3(MO 1-x PO4)2F 1+2x , 0≤x≤1, M is selected from at least one of Al, V, Ge, Fe, and Ga; or, the chemical formula of the phosphate is Na2MPO4F, and M is selected from at least one of Fe and Mn; The chemical formula of the sulfate is Na2M(SO4)2·2H2O, where M is selected from at least one of Cr, Fe, Co, Ni, Cu, Mn, Sn, Mo, Sb, and V.
14. The sodium ion battery according to claim 13, characterized in that: The layered transition metal oxide is selected from NaNi m Fe n Mn p At least one of O2 or NaNimConMnpO2, wherein m+n+p=1, 0≤m≤1, 0≤n≤1, 0≤p≤1.
15. The sodium ion battery according to claim 13, characterized in that: The Prussian material is selected from NaxMn[Fe(CN)6] y ·zH2O or Na x Fe[Fe(CN)6] y At least one of zH2O.
16. The sodium ion battery according to claim 13, characterized in that: The phosphate is selected from at least one of Na3(VPO4)2F3 and Na3(VOPO4)2F.
17. The sodium ion battery according to claim 13, characterized in that: The phosphate is selected from at least one of Na2FePO4F or Na2MnPO4F.
Citation Information
Patent Citations
Anode active substance, production method thereof, and lithium ion battery employing anode active substance
CN102496714A
Sodium ion battery negative electrode slurry, preparation method thereof, and negative electrode plate
CN107170957A